The Role of Social Capital in Promoting Economic Independence Among Fishermen in Krui, West Coast - Miftahurrizki, Miftahurrizki; Syafril, Syafrimen (The Eastasouth Journal of Social Science and Humanities, 2025)
Social capital the connections, shared values, and trust that foster collaboration between people and communities plays a crucial role in driving economic growth and self-sufficiency. First introduced by sociologist J.S. Coleman in 1985, the concept refers to the benefits that emerge from personal relationships and the networks people belong to. However, leaning too much on social capital for economic progress comes with its own set of risks. Given how interconnected African economies are, along with the globalized nature of modern trade, economic and political instability can spread quickly. That’s why any plan to tackle the challenges tied to social capital and economic independence must take regional dynamics into account. A common strategy focuses on three key areas: boosting economic development while ensuring environmental sustainability. The fishing communities along Krui’s Central Coast have developed distinct traits shaped by their long struggle with survival, economic instability, and environmental pressures. Over time, their way of life has been influenced by the delicate balance between relying on natural resources and facing the harsh realities of exploitation particularly the harvesting of puerulus, which has directly affected their livelihoods. Studies in this region have explored property rights and local narratives to grasp how these challenges have reshaped their economic and social dynamics. One key issue is the tension between economic self-sufficiency and the willingness to adapt to formal job requirements. Many in these communities prioritize independence over pursuing structured employment opportunities. This highlights the need for policies that support sustainable independence not just for individual fishers, but for their communities and the broader national economy. Another critical factor is social capital the trust, cooperation, and community bonds that hold these groups together. Research shows that strong social ties foster economic growth by creating trust among people. Unlike financial incentives, this trust stems from deeply ingrained cultural values and shared experiences, making it a powerful driver of resilience and progress.